Subsistence farming systems in Tehri district of Garhwal Himalaya in Uttarakhand, India - Negi, A.K.; Chauhan, D.S.; Todaria, N.P.; Rawat, M.S.S. (Indian Journal of Agroforestry, 2020)
Garhwal Himalaya on the northwest of India is a mountainous region where subsistence economy of rural people has traditionally been based on forests and agriculture. The traditional system of farming involves combine production of food, fodder, tree crops and livestock. The land use system shows that irrigated land is a very small fraction of the total agricultural land. Addressing the twin problems of water resource management and soil conservation are key to the economic prosperity of the region. Maximum numbers of villages are distributed in between 1000-1500 m altitude due to the gentle slope, moderate climate, and the availability of streams and rivers. Soil loss due to complex hill topography has increased the problem of agricultural production. Farmers do not have means to adopt soil conservation measures. Extension efforts in agriculture, soil conservation and forestry are negligible. Mixed cropping on small terraced field and homestead farming are the key components of subsistence farming system in the area. A proper holistic approach in land related activities are needed.